Biomonitoring of Multiple Mycotoxins in Urine by GC–MS/MS: A Pilot Study on Patients with Esophageal Cancer in Golestan Province, Northeastern Iran - Farhad Niknejad (Toxins, 2021)
A pilot study to investigate the occurrence of 10 mycotoxins (deoxynivalenol, DON; 3-acetyldeoxynivalenol, 3-ADON; 15-acetyldeoxynivalenol, 15-ADON; fusarenon-X, FUS-X; diacetoxyscirpenol, DAS; nivalenol, NIV; neosolaniol, NEO; zearalenone, ZON; zearalanone, ZAN; T-2 toxin, T-2; and HT-2 toxin, HT-2) in esophageal cancer patients was performed with the urinary biomarkers approach in Golestan, Iran. Urine multimycotoxin analysis was performed by dispersive liquid–liquid microextraction and gas chromatography–tandem mass spectrometry (GC–MS/MS) analysis, and values were normalized with urinary creatinine (μg/g). Four mycotoxins, namely NEO (40%), HT-2 (17.6%), DON (10%), and HT-2 (5.8%), were detected in the analyzed urine samples. DON was only detected in the control group (5.09 μg/g creatinine), while T-2 (44.70 μg/g creatinine) was only present in the esophageal cancer group. NEO and HT-2 were quantified in both control and case groups, showing average of positive samples of 9.09 and 10.45 μg/g creatinine for NEO and 16.81 and 29.09 μg/g creatinine for HT-2, respectively. Mycotoxin co-occurrence was observed in three samples as binary (NEO/HT-2 and T-2/HT-2) and ternary (DON/NEO/HT-2) combinations, reaching total concentrations of 44.58, 79.13, and 30.04 µg/g creatinine, respectively. Further investigations are needed to explore a causal association between mycotoxin contamination and esophageal cancer. For this pilot study in Golestan, the low sample size was a very limiting factor.